Reinstatement of species belonging Marphysa sanguinea complex (Annelida: Eunicidae) and description of new species from the mid-Pacific Ocean and the Adriatic Sea - Molina-Acevedo, Isabel C.; Idris, Izwandy (Zootaxa, 2020)
Marphysa sanguinea Montagu, 1813, the type species of genus Marphysa, was described with few characteristics and subsequently reported in tropical and temperate waters as a cosmopolitan species. Recent comparative studies have shown that M. sanguinea has a limited distribution to the Northeast Atlantic. As a result, species from the tropical and subtropical zones are now being redescribed as new species. However, this issue is not completely resolved because of the taxonomic status of seven nominal species, considered as junior synonymies of M. sanguinea. Herein, we examined the type and additional materials from five species in synonymy M. sanguinea and performed a compared analysis with the neotype of M. sanguinea. Additionally, we reviewed specimens from two localities in the mid-Pacific Ocean and the Adriatic Sea, where M. sanguinea was previously reported. As a result of this study, three species were reinstated (M. californica Moore, 1909, M. leidii de Quatrefages, 1866, and M. parishii Baird, 1869) and two subspecies, are now raised to species level (M. americana n. status and M. brevibranchiata n. status). In addition, two new species from Hawaii and Croatia are described: M. baileybrockae n. sp. and M. birgeri n. sp., respectively. Morphological comparisons with most species currently assigned to the M. sanguinea complex are presented. This work provides more support for rejecting the hypothesis that M. sanguinea is a cosmopolitan species and we encourage the use of novel and traditional morphological characters to differentiate species within the complex.